정상안압녹내장과 원발개방각녹내장에서 24시간 활동혈압의 차이 - 박창준; Chang Jun Park; 이남호; Nam Ho Lee; 김창식; Chang Sik Kim (Daihan angwa haghoi jabji, 2007)
목적: 정상안압녹내장과 원발개방각녹내장 환자에서 24시간 활동혈압의 차이에 대해 알아보았다. 대상과 방법: 정상안압녹내장 30명, 원발개방각녹내장 30명, 대조군 30명을 대상으로 24시간 활동혈압을 측정하여 각종 혈압인자의 차이에 대해 알아보았다. 결과: 야간 최저이완기혈압과 야간 최저평균동맥압은 정상안압녹내장에서 51.9±11.3 mmHg와 66.9±13.1 mmHg로 원발개방각녹내장(60.0±11.4 mmHg와 77.8±16.8 mmHg, p=0.048와 0.024)과 대조군(60.1±10.5 mmHg와 77.4±13.3 mmHg, p=0.047와 0.031)보다 유의하게 낮았다. 최저평균동맥압이 60 mmHg 미만인 경우가 정상안압녹내장(8명, 27%)이 원발개방각녹내장(2명, 7%)과 대조군(2명, 7%)보다 유의하게 많았다(p=0.038, p=0.038). 이완기혈압의 15%이상 dipper가 정상안압녹내장(17명, 57%)에서 원발개방각녹내장(9명, 30%)과 대조군(9명, 30%)보다 유의하게 많았다(p=0.037, p=0.037). 결론: 상당수 정상안압녹내장 환자에서 야간의 낮은 혈압이 녹내장 유발에 영향을 미칠 가능성이 있어, 야간혈압이 정상안압녹내장의 진단과 치료에 중요한 참고자료로 이용될 수 있겠다. <한안지 48(11):1512-1521, 2007> Purpose: To evaluate the variation of 24-hours blood pressure in patients with normal tension glaucoma (NTG) and primary open-angle glaucoma (POAG). Methods: Thirty patients with NTG, 30 patients with POAG, and 30 normal controls were enrolled in this study. Each subjects underwent 24-hours ambulatory blood pressure monitoring. The variation of each parameter and difference among NTG, POAG, and control groups were compared. Results: The lowest diastolic blood pressure (DBP) and the lowest mean arterial blood pressure (MAP) were significantly lower in the NTG group(51.9±11.3 mmHg and 66.9±13.1 mmHg) than in the POAG group(60.0±11.4 mmHg and 77.8±16.8 mmHg, p=0.048 and 0.024) and the control group(60.1±10.5 mmHg and 77.4±13.3 mmHg, p=0.047 and 0.031) during nighttime. More patients showed a lowest MAP less than 60 mmHg in the NTG group(8 patients, 27%) than in the POAG group(2 patients, 7%) and the control group(2 subjects, 7%, p=0.038 each). In addition, a decrease of more than 15% in DBP was more frequent in NTG group(17 patients, 57%) than in the POAG group(9 patients, 30%) and the control group(9 subjects, 30%, p=0.037 each). Conclusions: Nocturnal reduction in blood pressure may play an important role in the pathogenesis of NTG in some patients. Therefore, nighttime blood pressure should be considered as an important reference factor in diagnosis and treatment of NTG. J Korean Ophthalmol Soc 48(11):1512-1521, 2007